Kriteria Pembatasan Hak Cipta Lagu Dalam Praktik Covering Melalui Youtube - Faghlaifi Naim (JIPRO: Journal of Intellectual Property, 2019)
This study aims to find out the Criteria for Song Copyright Restriction in Covering Practices through Youtube. The formulation of the problem proposed is namely : What is The Criteria for Song Copyright Restriction in Covering Practices through Youtube. This study included a normative research typology. This normative legal research is doctrinal legal research. also referred to as library research or document study. It is called doctrinal law research because this research is carried out or aimed only at written regulations or other legal materials. It is called doctrinal law research because this research is carried out or aimed only at written regulations or other legal materials. Primary legal material is material that has juridical binding powers, such as legislation, court decisions, and agreements. Secondary legal materials are materials that do not have juridical binding powers, such as: draft legislation, literatures, and journals. Tertiary legal materials are complementary to primary data and secondary data, such as dictionaries and encyclopedias. Analysis is carried out with approaches including: legislation, conceptual, historical, comparative, and philosophical. The results of this study indicate that there are criteria for copyright restrictions in the internal YouTube regulations that must be considered to practice music covering.